Functional biodiversity of lipids in Antarctic zooplankton: Calanoides acutus, Calanus propinquus, Thysanoessa macrura and Euphausia crystallorophias - Falk-Petersen, Stig; Sargent, John R; Lønne, Ole Jørgen; Timofeev, Sergej (Polar Biology, 1999)
Zooplankton samples were collected in January 1993 off Dronning Maud Land along a transect from open waters to the marginal ice zone close to the Antarctic ice shelf. Thysanoessa macrura was caught in open waters while Calanoides acutus and Calanus propinquus were mainly sampled between ice floes in the marginal ice zone. The “ice-krill”Euphausia crystallorophias was found over the shelf directly associated with ice floes. T. macrura had a lipid content up to 36% of its dry weight with the dominant lipid class, wax ester, accounting for 45–50% of the total lipid. The predominance of 18:1 fatty alcohols is the striking characteristic of the wax esters. Small specimens of E. crystallorophias had lipid levels up to 26% of their dry weight with, unexpectedly, triacylglycerols being the dominant lipid (up to 41% of total lipid). The small levels of wax esters in these animals (3–6% of total lipid) had phytol as a major constituent. Large specimens of E. crystallorophias had up to 34% of their dry weight as lipid, with wax esters (47% of total lipid) dominated by 16:0 and 14:0 fatty alcohols as the major lipid. Calanus propinquus had lipid levels of up to 34% of their dry weight, with triacylglycerols (up to 63% of total lipid) being the dominant lipid. High levels of 22:1 (n-9) fatty acid were present in the triacylglycerols. Calanoides acutus had lipid levels up to 35% of the dry weight with wax esters accounting for up to 83% of total lipid. High levels of (n-3) polyunsaturated fatty acids were recorded with 20:5(n-3), 22:6(n-3) and 18:4(n-3) being the dominant moieties. On the basis of their lipid compositions we deduce that: (1) Calanoides acutus is the strictest herbivore among the four species studied, heavily utilizing the typical spring bloom; (2) T. macrura is essentially omnivorous, probably utilizing the less defined bloom situations found in oceanic waters; (3) E. crystallorophias is an omnivore well adapted to utilize both a bloom situation and to feed on ice algae and micro-zooplankton associated with the ice; (4) Calanus propinquus seems to be the most opportunistic feeder of the four species studied, probably grazing heavily on phytoplankton during a bloom and, during the rest of the year, feeding on whatever material is available, including particulates, flagellates and other ice-associated algae. We conclude that the different biochemical pathways generating large oil reserves of different compositions, enabling species to utilize different ecological niches, are major determinants of biodiversity in polar zooplankton.
Keywords: NARE 1992/93; Sørishavet; biodiversitet; biokjemi; dyreplankton; krill; lipider; marin biologi; zooplankton

Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Productivity in the southern Weddell Sea in the Austral summer - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum; Seim, Bjørnar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; alger; fytoplankton; krill

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

Krill Enzymes. A New Concept for Efficient Debridement of Necrotic Ulcers - Hellgren, L.; Karlstam, B.; Mohr, Viggo; Vincent, J. (International Journal of Dermatology, 1991)
The article discusses the new concept for surgery of necrotic ulcers using the krill enzymes. The krill peptide hydrolases represent a new and important alternative to mammalian or microbial enzymes for distinctive medical applications, such as debridemen.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Genetic homogeneity of krill (Euphausia superba Dana) in the Southern Ocean - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1989)
Development of a comprehensive picture of the genetic population structure of the Antarctic krill (Euphausia superba) has been hampered by a lack of genetic data from two major areas of the species' distribution, the Bellingshausen Sea and the Ross Sea. Evidence from earlier studies of a discrete “Bellingshausen Sea” population was based on anomalous allele frequencies in two sample sets that were collected near the west coast of the Antarctic Peninsula rather than in the Bellingshausen Sea proper. In this paper we describe the first biochemical genetic data obtained on krill from the central Bellingshausen Sea and from the Ross Sea. Analyses of eight polymorphic loci in samples from these two areas have failed to provide any evidence of population structuring within the Pacific sector of the Southern Ocean, and have indicated that Pacific sector krill cannot be genetically discriminated from Atlantic sector krill or Indian Ocean sector krill. These findings further support the hypothesis of a single circumpolar breeding population of Antarctic krill.
Keywords: Rosshavet; Sørishavet; biokjemi; genetikk; krill; marin biologi; plankton

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton

Biochemical genetics and population structure of Euphausia superba - Fevolden, Svein Erik (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1988)
Keywords: Sørishavet; biokjemi; krill; plankton

Genetic population structure of Euphausia superba DANA in the Atlantic Sector of the Southern Ocean as demonstrated by different electrophoretic techniques - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1988)
Electrophoretic analyses of allele distributions at nine polymorphic gene loci were conducted in samples of Euphausia superba from the Bransfield Strait, off the South Orkney Islands, and from the south-eastern part of the Weddell Sea. The aim was to determine whether reported phenotypic differences between krill stocks from these areas could be linked to genotypic differences. Despite minor deviations of genotype distributions from Hardy-Weinberg expectations, the data gave no evidence of genetic heterogeneity over the sampled area, and the hypothesis of a single genetically homogeneous krill population could not be rejected. Genetic data for four selected loci were verified by using two different electrophoretic methods. Results from these two techniques yielded no discrepancies in interpretation of the data.
Keywords: Sør-Orknøyene; Sørishavet; Weddellhavet; genetikk; krill; marin biologi; plankton

Biochemistry of the autolytic processes in Antarctic krill post mortem. Autoproteolysis - Ellingsen, Trond E.; Mohr, Viggo (Biochemical Journal, 1987)
1. Autoproteolysis post mortem was examined at 0 degree C by following the changes in the major classes of krill (Euphausia superba and Euphausia crystallorophias) proteins and by liberation of peptides and free amino acids, and was based on experiments conducted on board expedition vessels in the Antarctic. 2. Primarily salt-soluble proteins were broken down during the first week of incubation, whereas water-soluble and insoluble proteins were degraded to a much smaller extent. The enzymes responsible for the hydrolysis presumably originate primarily from the digestive apparatus of the krill. 3. In general, the individual amino acids were released at rates corresponding to their relative occurrence in the bulk protein of the krill. Alanine was liberated in larger amounts than would be expected from the composition of the krill protein, and was evidently formed also by reactions other than proteolysis. Glutamic acid, and certain amino acids which presumably occur with high frequency adjacent to glumatic acid residues in the krill protein, were liberated only to a limited extent, and accumulated in smaller peptides. 4. During proteolysis, arginine seemed to be converted to some degree into ornithine, and on prolonged incubation conversion of arginine and lysine into their corresponding decarboxylation products, agmatine and cadaverine, appeared to take place.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Genetic variation of Euphausia superba Dana in the Antarctic Peninsula waters - Fevolden, Svein Erik (Sarsia, 1986)
Nine samples of Antarctic krill collected at seven localities in the Palmer Archipelago and Bransfield Strait west of the Antarctic Peninsula were analysed for genetic variation at eight enzyme loci. Despite significant among sample heterogeneity in allele frequencies, no convincing evidence was found to support the hypothesis of distinct genetic stocks of Euphausia superba in the investigated area. Allele frequency distributions could not be correlated to regional differences in size patterns. Allelic proportions at the PGI locus did not indicate that the investigated krill was genetically different from E. superba from the Weddell Sea region (from earlier investigations). Deviations of genotypes, or allele frequencies from those expected under Hardy-Weinberg equilibrium, however, may indicate regional, or yearly variation due to occasional selection.
Keywords: Sørishavet; Weddellhavet; genetikk; krill; plankton

Proteases of Antarctic krill—a new system for effective enzymatic debridement of necrotic ulcerations - Hellgren, L.; Mohr, Viggo; Vincent, J. (Experientia, 1986)
The Antarctic krill (Euphausia superba) possesses an ‘over-dimensioned’ digestive system, which is of vital importance for the survival of this euphaucean shrimp in the extreme marine environment. The isolated enzymes contain a well-balanced mixture of both endo- and exopeptidases, assuring fast and complete breakdown of proteinaceous material. These unique properties have now been shown to be extremely valuable for the effective removal of necrotic debris, fibrin or blood crusts in vitro. Therefore the krill enzymes should be considered as an important resource in the future management of necrotic wounds.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The distribution of lipid in the tissues of Antarctic krill, Euphausia superba - Saether, Olav; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. The distribution of lipid in the tissues of Euphausia superba has been examined by histological and chemical methods. 2. The total lipid content of krill from different catches may vary considerably, and the variations are probably due both to differences in nutritional status and maturity of the roe of female krill. 3. Female krill contained about twice as much lipid as male krill from the same haul. 4. The roe is the dominating lipid depot in female krill; in both male and female krill lipid-rich areas are found along the digestive tract, between muscle bundles and beneath the exoskeleton. 5. Both the phosphoglyceride- and triacylglycerol content of body fractions of E. superba varied in proportion to the total lipid content, thus supporting the contention that both phosphoglycerides and triacylglycerols serve as depot lipids in this species of krill.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

Factors Governing Pelagic Production in Polar Oceans - Sakshaug, Egil; Holm-Hansen, Osmund (Marine Phytoplankton and Productivity: Proceedings of the invited lectures to a symposium organized within the 5th conference of the European Society for Comparative Physiology and Biochemistry — Taormina, Sicily, Italy, September 5–8, 1983, 1984)
Keywords: Sørishavet; fytoplankton; havis; krill; planteplankton; primærproduksjon; sjøis; sjøvann

Biokjemiske studier over antarktisk krill - Ellingsen, Trond E; Norges tekniske høgskole Institutt for teknisk, biokjemi (Institutt for teknisk biokjemi, 1982)
Keywords: Bouvetøya; Sørishavet; Weddellhavet; biokjemi; krill; lipider; lyskreps; marinbiologi

Krill: mat i mengder i Sørishavet - Sakshaug, Egil (Syn og segn, 1982)
Keywords: Sørishavet; krill; marinbiologi

Enzyme polymorphism in Antarctic krill (Euphausiacea); genetic variation between populations and species - Fevolden, Svein Erik; Ayala, Fransisco J. (Sarsia, 1981)
By means of enzyme electrophoretical assays three samples of Euphausia superba, all from the Atlantic sector of the Antarctic Ocean, were examined to see whether or not they represent genetically separated populations. The same samples were also compared with E. superba from off the Western coast of the Antarctic Peninsula, representing the Pacific sector. The latter animals have previously been studied by other authors. One sample of a second species of Antarctic krill, E. crystallorophias, was likewise examined. Thirty-five loci were studied in E. superba, and it is concluded that the three samples from the Atlantic sector most probably do not represent reproductively isolated populations. Their average heterozygosity, about 10%, is however greater than the value previously found for the ‘Pacific’ E. superba, 5.8 %. Calculations of the genetic identity and genetic distance between the Atlantic and ‘Pacific’ samples of E. superba suggest they represent separate populations. The average heterozygosity of E. crystallorophias was estimated to be between 9.1 and 9.4 %, from studies of 33 loci. The genetic distance between this species and E. superba was estimated at 0.989. The results are finally discussed in terms of postulated theories on genetic variability versus environmental heterogeneity.
Keywords: NARE 1976/77; NARE 1978/79; Sørishavet; genetikk; krill; marin biologi; plankton

Bacteriologigal characteristics of Antarctic krill (Crustacea, Euphausiacea) - Fevolden, Svein Erik; Eidså, Gudmunn (Sarsia, 1981)
The bacterial flora of two species of Antarctic krill, Euphausia superba Dana and E. crystallorophias Holt & Tattersall, was studied with the aim of investigating the role played by bacteria during the claimed rapid deterioration of these animals. The number of bacteria on fresh krill was characterized as low, but started to increase exponentially after a few days of storage at low temperatures. Dominant species were of the genera Moraxella, Pseudomonas, and Alteromonas. Comparing the low initial number of bacteria with the high autolytic activity it is suggested that the rapid degradation of krill during the first days of storage is induced by autolysis and not by bacterial activity.
Keywords: Sørishavet; biokjemi; krill; lyskreps; marin biologi; plankton

Krill off Bouvetøya and in the southern Weddell Sea with a description of larval stages of Euphausia crystallorophias - Fevolden, Svein Erik (Sarsia, 1980)
In the austral summer 1978/79 samples of krill were taken off Bouvetøya and in the southern Weddell Sea. Off Bouvetøya Euphausia superba Dana was the dominant species, but the population pattern indicates that the individuals found there were expatriates from other areas. For the first time larvae of E. superba were found in significant amounts in the southern Weddell Sea. Except from shallow water and the most southern position, they were equal in abundance to the larvae of E. crystallorophias Holt & Tattersall. Larval stages of the latter are described as is the successive spawning that takes place among the three species of krill found in the southern Weddell Sea.
Keywords: Bouvetøya; NARE 1978/79; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

On the Antarctic euphasiids from the "Norvegia" expeditions 1929-30 and 1930-31 - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Norvegia ekspedisjoner; euphausider; forskning; hydrografi; krill; marin biologi; plankton; zoologi

On the biology of some southern Copepoda - Ottestad, Per (I kommisjon hos Dybwad, 1932)
Keywords: S.S.Vikingen; Sørishavet; Weddellhavet; hoppekreps; hydrografi; krill; marin biologi; plankton

On the biology of southern Euphausiidae - Ruud, Johan Tidemand (Dybwad, 1932)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

Euphasiacea : with notes in their biogeography and development - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; forskning; krepsdyr; krill; marin biologi; plankton; zoologi

Nitrates and Phosphates in the Southern Seas - Ruud, Johan T (ICES Journal of Marine Science, 1930)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hval; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton